2002
DOI: 10.1111/1467-8624.t01-1-00511
|View full text |Cite
|
Sign up to set email alerts
|

How Money Matters for Young Children's Development: Parental Investment and Family Processes

Abstract: This study used data from the Panel Study of Income Dynamics and its 1997 Child Development Supplement to examine how family income matters for young children's development. The sample included 753 children who were between ages 3 and 5 years in 1997. Two sets of mediating factors were examined that reflect two dominating views in the literature: (1) the investment perspective, and (2) the family process perspective. The study examined how two measures of income (stability and level) were associated with presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

59
826
5
21

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 945 publications
(911 citation statements)
references
References 67 publications
59
826
5
21
Order By: Relevance
“…23 The scales have been used to evaluate effects of early childhood nutritional interventions and early health insults on cognitive development in children, 24 and were selected because they have shown sensitivity to an income intervention in low income families, 25 and to outcomes in children born with low birth weight. 26 Scores were log-transformed due to positive skew.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 3 more Smart Citations
“…23 The scales have been used to evaluate effects of early childhood nutritional interventions and early health insults on cognitive development in children, 24 and were selected because they have shown sensitivity to an income intervention in low income families, 25 and to outcomes in children born with low birth weight. 26 Scores were log-transformed due to positive skew.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…25,[45][46][47][48] Nonetheless, the relevance of this comparison may be questionable given the non-comparability of the populations and the diverse nature of the interventions. Studies in the developing world aiming to improve cognitive development in very low income populations have focused on nutritional interventions 49 or on early childhood development interventions, 50 and evidence of an association between income change and developmental outcomes in this context is scarce.…”
Section: Cognitive Motor and Language Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported that positive, involved, and responsive parenting apparently buffers the negative impact of risk exposure on academic achievement and social skills for preschoolers in rural areas (Brody, Murray, Kim, & Brown, 2002), during the transition to school for African American children in suburban areas (Burchinal et al, 2006), and in middle and high school (Garmezy, 1993;Grotevant, 1998;Gutman, Sameroff, & Eccles, 2002). Exposure to social risk is much less related to preschool-or school-age outcomes when parents are positive, involved, and responsive (Brody et al, 2002;Burchinal et al, 2006;Krishnakumar & Black, 2002;Masten et al, 1999;Yeung, Linver, & Brooks-Gunn, 2002). Therefore, a third goal of our study was to test whether access to stimulating materials, warm and sensitive motherchild interactions, and the size of the mother's vocabulary in mother -child interactions serve as protective factors for cognitive development in infancy.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%